A Companion to the Environmental History of Byzantium
1 online resource (565 pages)
Keywords: How did humans and the environment impact each other in the medieval Eastern Mediterranean? How did global climatic fluctuations affect the Byzantine Empire over the course of a millennium? And how did the transmission of pathogens across long distances affect humans and animals during this period? This book tackles these and other questions about the intersection of human and natural history in a systematic way. Bringing together analyses of historical, archaeological, and natural scientific evidence, specialists from across these fields have contributed to this volume to outline the new discipline of Byzantine environmental history. Contributors are: Johan Bakker, Henriette Baron, Chryssa Bourbou, James Crow, Michael J. Decker, Warren J. Eastwood, Dominik Fleitmann, John Haldon, Adam Izdebski, Eva Kaptijn, Jürg Luterbacher, Henry Maguire, Mischa Meier, Lee Mordechai, Jeroen Poblome, Johannes Preiser-Kapeller, Abigail Sargent, Peter Talloen, Costas Tsiamis, Ralf Vandam, Myrto Veikou, Sam White, and Elena Xoplaki